Impact of hormone receptor status and distant recurrence-free interval on survival benefits from trastuzumab in HER2-positive metastatic breast cancer. Issue 1 (December 2017) - Yang, Hai-Yuan; Ma, Ding; Liu, Yi-Rong; Hu, Xin; Zhang, Jian; Wang, Zhong-Hua; Di, Gen-Hong; Hu, Xi-Chun; Shao, Zhi-Ming
Abstract We sought to investigate the impact of hormone receptor (HR) status and distant recurrence-free interval (DRFI) on the degree of overall survival (OS) benefit from palliative trastuzumab-containing treatment in HER2-positive metastatic breast cancer (MBC). Here, we retrospectively identified 588 eligible HER2-positive patients with postoperative distant recurrence. DRFI of HR+HER2+ MBC patients (median: 30.7 months, IQR: 18.5–45.9, P  < 0.001) was significant longer compared with HR−HER2+ patients. Patients were categorized into four subgroups based on HR status and palliative trastuzumab (trast+) received. The most superior outcome was observed in the HR+HER2+trast+ subgroup, with a median OS of 48.3 months. Moreover, DRFI > 24 months is an independent favourable prognostic factor for both HR−HER2+ patients (Hazard Ratio (HzR) = 0.55, 95% CI: 0.39–0.76, P  < 0.001) and HR+HER2+ patients (HzR = 0.45, 95% CI: 0.32–0.64, P  <  0 .001 ). Upon further analysis of the interaction between trastuzumab and DRFI, the degree of trastuzumab benefits in HR−HER2+ MBC patients remained basically unchanged regardless of DRFI length. Unlikely, the degree in HR+HER2+ MBC patients decreased gradually along with DRFI extending, indicating that trastuzumab failed to translate into an OS benefit for late recurrent (DRFI > 5years) HR+HER2+ MBC patients.